Leadership preparation for new and aspiring high school principals: a case study in south-west China - Xue, Sarah Shan (2021)
In 2013, the Ministry of Education in China launched a set of National Qualifications and Standards for Headship in China, which aimed at guiding and supporting the professional development of principals in China. This is also the first time that the concept of the professionalisation of principals was documented by policymakers. This thesis outlines research aimed at understanding the leadership preparation process, in terms of how new leaders were selected, recruited, and developed. Following the preparation process, the research also examined the impact of the preparation process, in terms of leadership enactment and principals’ socialization.